Peningkatan Pengetahuan dan Deteksi Dini Tanda Bahaya Kehamilan di Wilayah Kerja Puskesmas Sipahutar Kabupaten Tapanuli Utara Tahun 2022 - riance ujung; Dimpu Rismawaty Nainggolan (Jurnal Mitra Prima, 2022)
Early detection of danger signs and symptoms during pregnancy is the best effort to prevent serious disruption to pregnancy or the safety of pregnant women. Predisposing factors and the presence of comorbidities should also be recognized early on so that maximum efforts can be made to prevent serious disturbances to both pregnancy and the safety of the mother and the baby she is carrying. Community service activities in the form of providing health education on Early Detection of Danger Signs in Pregnancy were carried out to 76 pregnant women in 6 Classes of Pregnant Women in the Sipahutar Health Center Work Area, namely Siabal-abal Villages I, II, III, V and VI, Tapian Nauli II, Nihuta Fighting I, II and III. The activities carried out were pretest, health education, history taking and checking for signs of danger in pregnancy, namely blood pressure, temperature, fetal movement, edema, urine protein and post test. Based on the results of the pre and post test, it can be seen that there is an increase in the number of pregnant women who have good knowledge from 6 (7.90%) pregnant women at the time of the pre test to 31 people (40.79%), with sufficient knowledge of 49 people (64.47%). ) to 37 people (48.68%), while the number of pregnant women with less knowledge of pregnant women at the time of the pre test was 21 people (27.63%) at the time of the post test to 8 people (10.53%). From the examination of the danger signs in pregnancy, it was found that the results of high blood pressure were 3 people (3.95%). The activity went well and smoothly. Expected to pregnant women to always be aware of all risks of pregnancy complications by actively conducting early detection of any complications that will occur during pregnancy. In addition, pregnant women are also expected to take advantage of the Maternal and Child Health (KIA) book, in which the book also provides various kinds of danger signs of pregnancy that can occur in pregnant women.